Centralized Testing Facility Uniting Food Systems for Space Exploration - Kim, Kyunghwan; Blomqvist, Tor Adrian; Schubert, Daniel (International Astronautical Congress, 2024)
The EDEN ISS project, operational in Antarctica from 2015 to 2021, marked a significant advancement in bioregenerative life-support systems through plant cultivation in a Mobile Test Facility (MTF) under extreme conditions. This project plays a crucial role in addressing current space food system challenges, where balancing Earthsupplied food with on-site cultivation is essential. The limitations of resupply missions from Earth, including resource constraints and food acceptability, emphasize the need for an integrated space food production approach that spans from cultivation to consumption. This paper introduces the concept of a centralized testing facility designed to address existing research gaps in space food system for future human space missions. By integrating post-harvest management—including packaging, preservation, storage, and processing—with Lunar Agricultural Module (LAM), the facility aims to foster innovative research. Initial findings from the concept study are presented, alongside earlyphase design outcomes and the potential impact of advancing integrated plant cultivation and post-harvest management technologies. These innovations could also provide sustainable solutions for Earth’s food systems, drawing on lessons learned from agriculture in extreme environments.